2019
DOI: 10.1021/acs.orglett.9b00391
|View full text |Cite
|
Sign up to set email alerts
|

Formal Carbene C–H Bond Insertion in the Cu(I)-Catalyzed Reaction of Bis(trimethylsilyl)diazomethane with Benzoxazoles and Oxazoles

Abstract: A Cu(I)-catalyzed cross-coupling reaction of bis(trimethylsilyl)diazomethane and benzoxazoles/oxazoles is reported. A wide range of functional groups can be tolerated in this transformation. This reaction provides a new method to directly introduce a 1,1-bis(trimethylsilyl)methyl group into heteroaromatic C−H bonds. Subsequent transformations of 1,1-bis(trimethylsilyl)-methylated heteroaromatic compounds are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 , ppm): δ 7.29 (d, J = 7.0 Hz, 2H), 7.22 (s, 1H), 7.19−7.18 (m, 1H), 7.16−7.13 (m, 2H), 6.83 (d, J = 8.5 Hz, 2H), 6.59 (d, J = 8.5 Hz, 2H), 4.67 (t, J = 10.0 Hz, 1H), 4.26 (q, J = 7.0 Hz, 2H), 3.76 (s, 3H), 1.87 (s, 3H), 1.29 (t, J = 7.0 Hz, 3H). 13 C {1H} NMR (125.8 MHz, CDCl 3 , ppm): δ 193. 6, 160.9, 159.9, 136.6, 132.9, 131.9, 128.9, 128.2, 128.0, 115.4, 114.1, 98.4, 86.6, 75.6, 61.6, 55.3, 47.9, 29.0, 14.2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR (500 MHz, CDCl 3 , ppm): δ 7.29 (d, J = 7.0 Hz, 2H), 7.22 (s, 1H), 7.19−7.18 (m, 1H), 7.16−7.13 (m, 2H), 6.83 (d, J = 8.5 Hz, 2H), 6.59 (d, J = 8.5 Hz, 2H), 4.67 (t, J = 10.0 Hz, 1H), 4.26 (q, J = 7.0 Hz, 2H), 3.76 (s, 3H), 1.87 (s, 3H), 1.29 (t, J = 7.0 Hz, 3H). 13 C {1H} NMR (125.8 MHz, CDCl 3 , ppm): δ 193. 6, 160.9, 159.9, 136.6, 132.9, 131.9, 128.9, 128.2, 128.0, 115.4, 114.1, 98.4, 86.6, 75.6, 61.6, 55.3, 47.9, 29.0, 14.2.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 , ppm): δ 7.41 (d, J = 8.5 Hz, 2H), 7.29 (d, J = 7.5 Hz, 2H), 7.23 (t, J = 7.0 Hz, 2H), 7.18−7.15 (m, 1H), 7.00 (d, J = 8.5 Hz, 2H), 6.71 (d, J = 1.0 Hz, 1H), 4.62 (t, J = 7.0 Hz, 1H), 4.24 (q, J = 7.0 Hz, 2H), 3.41 (dd, J = 7.0, 17.0 Hz, 1H), 3.34 (dd, J = 8.5, 17.0 Hz, 1H), 2.22 (s, 3H), 1.28 (t, J = 7.0 Hz, 3H). 13 C {1H} NMR (125.8 MHz, CDCl 3 , ppm): δ 214.5, 196.0, 190.2, 161.3, 142.4, 132.1, 130.8, 128.6, 128.52, 127.8, 126.9, 122.1, 117.1, 100.6, 61.5, 45.0, 38.2, 27.6, 14.3. IR (KBr): 2136, 1715, 1683, 1302, 1011 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies indicated that the main step is the formation of a Cu(I) carbene species, followed by migratory insertion and protonation to produce the final products, as shown in Scheme 61. In 2019, Wang and coworkers exploited an economical Cu(I)-catalyst to achieve the cross-coupling of bis(trimethylsilyl)diazomethane and benzoxazoles/oxazoles, affording a series of 1,1-bis(trimethylsilyl)-methylated heteroaromatic compounds in moderate to good yields, through a carbene migratory insertion process [93]. Mechanistic studies indicated that the main step is the formation of a Cu(I) carbene species, followed by migratory insertion and protonation to produce the final products, as shown in Scheme 61.…”
Section: Scheme 55mentioning
confidence: 99%
“…This site-specific oxime synthesis could be potentially used in peptide and protein bioconjugation (Scheme C) . More importantly, despite the presence of reactive carbonyl functionality, the Pd­(PPh 3 ) 4 -catalyzed Suzuki–Miyaura cross-coupling reaction of compound 3f′ still proceeded successfully, leading to 3f″ in 98% yield and 96% deuterium incorporation (Scheme D) …”
mentioning
confidence: 99%